Identifying barriers to the availability and use of Magnesium Sulphate Injection in resource poor countries: A case study in Zambia - Hill Suzanne R; Bero Lisa A; Ridge Anna L (BMC, 2010)
Abstract Background Pre-eclampsia and eclampsia are serious complications of pregnancy and major causes of maternal mortality and morbidity worldwide. According to systematic reviews and WHO guidelines magnesium sulphate injection (MgSO4) should be the first -line treatment for severe pre-eclampsia and eclampsia. Studies have shown that this safe and effective medicine is unavailable and underutilized in many resource poor countries. The objective of this study was to identify barriers to the availability and use of MgSO4 in the Zambian Public Health System. Methods A 'fishbone' (Ishikawa) diagram listing probable facilitators to the availability and use of MgSO4 identified from the literature was used to develop an assessment tool. Barriers to availability and use of MgSO4 were assessed at the regulatory/government, supply, procurement, distribution, health facility and health professional levels. The assessment was completed during August 2008 using archival data, and observations at a pragmatic sample of health facilities providing obstetric services in Lusaka District, Zambia. Results The major barrier to the availability of MgSO4 within the public health system in Zambia was lack of procurement by the Ministry of Health. Other barriers identified included a lack of demand by health professionals at the health centre level and a lack of in-service training in the use of MgSO4. Where there was demand by obstetricians, magnesium sulphate injection was being procured from the private sector by the hospital pharmacy despite not being registered and licensed for use for the treatment of severe pre-eclampsia and eclampsia by the national Pharmaceutical Regulatory Authority. Conclusions The case study in Zambia highlights the complexities that underlie making essential medicines available and used appropriately. The fishbone diagram is a useful theoretical framework for illustrating the complexity of translating research findings into clinical practice. A better understanding of the supply system and of the pattern of demand for MgSO4 in Zambia should enable policy makers and stakeholders to develop and implement appropriate interventions to improve the availability and use of MgSO4.